(3GdeSFhdjI GdeOfjI GdfGTFI Yf GdaVGdI (B/ s - (3OGdjG GdSHGYj eMeO GdSHGYjs; (3fRjg eMeO GdUGOb GdegOi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2011)
(3JfGhdJ ai gPg GdQSGdI HMK ehVhY GdeSFhdjI GdeOfjI GdfGTFI Yf GdaVGdI(B: (3h HUaI NGUI eFhdjI GdaVhdi (B: (3HMK GdJWhQ GdJGQjNi ddaVGdI (B: (3h hbaJ Ydi GdJWhQ GdJGQjNi dacQI GdaVGdI(B. (3h cPdc GdJWhQ GdJGQjNi ddeSFhdjI GdeOfjI(B. (3YQVJ GdaVGdI ai Gdabg GdESdGei h GdbGfhf GdhVYi(B. (3YQVJ eSFhdjI GdaVhdi CeGe QH GdYed h CeGe GdZjQ(B. (3fJGFL aj JMOjO LhGfH GdeSFhdjI GdeOfjI GdfGTFI Yf GdaVGdI ef GdfGMjJjf GdfXQjI h GdYedjI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2011s
(3HHdjhLQGajG(B: (3UaMGJ (B303-324s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3GdaVGdIs; (3GdeOfjIs; (3GdeSFhdjIs; (3GdGKQGA HdG SHHs; (3GfhGY GdaVGdIs; (3GQcGf GdaVGdIs; (3GfbVGA GdaVGdIs; (3eSFhdjI GdaVhdjs; (3GdJRGeGJ GdaVhdjs; (3GdYbO Gdehbhas; (3NWG GdaVhdjs; (3GdbGfhf GdQheGfjs; (3GdbGfhf GdeOfj GdaQfSjs; (3GdTQjYI GdGSdGejIs; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs